2015
DOI: 10.1002/cbic.201402611
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lysozyme–Metallacarborane Conjugates and the Effect of Boron Cluster Modification on Protein Structure and Function

Abstract: Two complementary methods, "in solution" and "in solid state", for the synthesis of lysozyme modified with metallacarborane (cobalt bis(dicarbollide), Co(C2 B9 H11 )2 (2-) ) were developed. As metallacarborane donors, oxonium adducts of cobalt bis(dicarbollide) and 1,4-dioxane or tetrahydropyran were used. The physicochemical and biochemical properties of the obtained lysozyme-metallacarborane conjugates were studied for changes in secondary and tertiary structure, aggregation behavior, and biological activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The 1 H, 11 B, and 13 CNMR spectra were recorded with aB ruker AVANCE DRX 400 spectrometer.T he chemical shifts of 1 H, 11 B, and 13 Ca re reported in parts per million at 400. 13,128.38, and 100.63 MHz, respectively,w ith tetramethylsilane as internal standard and referencing to the unified scale. [22] Substituted boron atoms could be assigned by comparison of 11 Ba nd 11 B{ 1 H} NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H, 11 B, and 13 CNMR spectra were recorded with aB ruker AVANCE DRX 400 spectrometer.T he chemical shifts of 1 H, 11 B, and 13 Ca re reported in parts per million at 400. 13,128.38, and 100.63 MHz, respectively,w ith tetramethylsilane as internal standard and referencing to the unified scale. [22] Substituted boron atoms could be assigned by comparison of 11 Ba nd 11 B{ 1 H} NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…[12] In view of this large number of peptides,i ta ppears surprising that the cobalt bis(dicarbollide) anion 1 has never been incorporated into any tumor-selective peptided espite obvious possible advantages. [13] The high stabilityr elative to polyhedral boron compounds, the strongl ipophilicity (givingr ise to hydrophobic peptide-receptor interactions), the hydridic shell (whichf acilitatesu nusualm olecular interactions unknown in traditional organic scaffolds), and the large number of boron atomsm ake anion 1 an interesting moiety,i np articularf or applications in BNCT. [2a,b] The biologically active derivatives of cobaltb is(dicarbollide) that have previously been studied [3][4][5][6]13] have exclusively been obtained by ring-opening reactions of cyclic oxonium derivatives 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…As until today, the implications of protein coronas on the biological performance of (metalla)carboranes and borates as colloidal aggregators have hardly been studied, but some publications on metallacarborane-protein conjugates deal with adsorbed protein phaenomena (see, e. g., refs. [158] and [179]). The following sections will thus highlight selected effects of protein coronas on immune toxicity, active targeting, and cellular uptake and clearance pathways, and appropriate examples from the (metalla)carboranes literature will be briefly discussed.…”
Section: Protein Coronamentioning
confidence: 98%
“…Furthermore, loading capacity and binding sites are also determined using mass spectrometry methods or Western blot analyses, often in combination with chromatographic or electrophoretic separations, specifically for peptide, protein or enzyme conjugates. [162,176,[179][180][181] A rather atypical example is one of the latest works by Ventura, Teixidor and co-workers (2019) on the interaction between BSA and Na[COSAN]. [158] They used DLS, zeta potential and far-UV circular dichroism (CD) spectroscopy to infer saturation stoichiometry and co-assembly motifs of BSA-COSAN nanostructures, concluding that COSAN molecules, when used in large excess (100 ×) over BSA, can form a sort of protective crown around the BSA molecule, shielding it from thermal and light-induced denaturation and acetylation.…”
Section: Chemical Stability: Drug Loading and Leakagementioning
confidence: 99%
“…It was demonstrated that they provide an unusual interaction potential resulting in self-assembly in solution 5,6 and complexation with various nanosystems. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] They are utilized, for example, for ion extraction 26 and recently also in medicinal chemistry. [27][28][29][30][31][32][33][34][35][36][37][38] As regards medical applications, our interest is targeted to the preparation of stimuli-responsive hybrid nanosystems consisting of a nano-organized polymer matrix with embedded metallacarborane clusters, [39][40][41][42] which would lead to biocompatible vessels for drug-delivery purposes.…”
Section: Introductionmentioning
confidence: 99%